2022
DOI: 10.1002/mma.8252
|View full text |Cite
|
Sign up to set email alerts
|

Concept and solution of digital twin based on a Stieltjes differential equation

Abstract: We introduce the concept of a digital twin by using Stieltjes differential equations. A precise mathematical definition of solution to the problem is presented. We also analyze the existence and uniqueness of solutions, introduce the concept of main digital twin. As a particular case, the classical compartmental SIR (susceptible, infected, recovered) epidemic model is considered and we study the interrelation between the digital twin and the system. In doing so, we use Stieltjes derivatives to feed the data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…where k is a fixed positive integer, the coefficients α j are strictly positive and (1) and if λ = lim n→∞ x n then x n ≤ kλ for all n ≥ 1.…”
Section: Convergence Results Under Convexity Conditions On the Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…where k is a fixed positive integer, the coefficients α j are strictly positive and (1) and if λ = lim n→∞ x n then x n ≤ kλ for all n ≥ 1.…”
Section: Convergence Results Under Convexity Conditions On the Functionsmentioning
confidence: 99%
“…Measure differential equations (which can be equivalently written as Stieltjes differential equations, see [19], [27]) proved themselves very useful in studying real life processes with dead times or abrupt changes occurring in their dynamics, e.g. [1], [19] or [29].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, the authors of [14] explored the FTS of a differential system with impulsive conditions by utilizing a delayed form of exponential function. Some recent noteworthy work on the FTS analysis of dynamical systems can be found in [30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study showed that awareness-raising controls could further reduce the number of COVID-19 infections. There are also many important literatures about COVID-19, please refer to [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] .…”
Section: Introductionmentioning
confidence: 99%